Revenue Autonomy and Entrepreneurship in The Municipalities of the Warmian-Masurian Voivodeship - Wichowska, Anna; Wierzejski, Tomasz (Olsztyn Economic Journal, 2019)
One of the most important problems in the proper functioning and fulfillment of entrusted tasks by municipalities in Poland is their high income independence. It depends, inter alia, on the broadly understood entrepreneurship undertaken in their area. Therefore the aim of this study was to identify the factors affecting entrepreneurship in the Warmian-Masurian Voivodeship in 2014–2016, which determined the revenue autonomy of municipalities in the region. The analysis was conducted with the use of a multiple linear regression model. Revenue autonomy, which is measured by the proportion of a municipality’s own-source revenues in total revenues, was the explained (dependent) variable. The initial group of explanatory (independent) variables consisted of 22 indicators linked with the operations of local businesses in the evaluated region. The key determinants of the revenue autonomy of municipalities were: the percentage of commercial partnerships in the total number of companies in the private sector, the percentage of private-sector companies in the total number of companies, the percentage of industrial and construction companies in the total number of companies, the percentage of self-employed in the total number of companies in the private sector, the number of agricultural producers, livestock breeders and hunting companies per 1000 residents, and the number of companies employing up to 9 people per 10,000 working-age residents.